Local piezo-response for lead-free Ba0.9Ca0.1Ti0.9Zr0.1O3 electro-ceramic by switching spectroscopy - Herrera-Pérez,Guillermo (2018)
The purpose of this work is to determine the effective piezoelectric coefficient (d33) and the macro ferroelectric hysteresis behavior for the Ba0.9Ca0.1Ti0.9Zr0.1O3 (BCZT). The sample was prepared by the modified Pechini method and it was sintered at 1250 ºC for 5 h. The refinements of X-ray diffraction (XRD) patterns obtained by the Rietveld method suggest a slight degree of tetragonality (c/a = 1.0025) in the perovskite structure. High counting statistics was performed in the two-dimensional grazing incidence 2D-GIXRD characterization by using synchrotron radiation. These results and the Raman spectrum analysis support the XRD interpretation. The morphology reveals a non-homogeneous terrace-type shape with a grain size distribution centered at 13 microns. The switching spectroscopy piezo-response force microscopy was used to obtained the effective d33 = 142 pm/V. The soft ferroelectric hysteresis shows a coercive field Hc = 1.3 kV/cm with a saturation polarization Ps = 15.7 µC/cm2.